Legal Analysis of Co-Branding as an Identity for Creative Economy Products in Bangkalan Regency - Kumala, Tannia Dinda; Abdulovna, Daryna Dzemish (Legalis : Journal of Law Review, 2024)
Intellectual property rights provide exclusive protection as in brand protection. By registering a brand, a creative economy product will receive repressive legal protection, obstacles in brand registration are experienced by some creative economy actors in Bangkalan Regency. Until now, there has been no regional legal product regarding intellectual property protection, especially convenience through the concept of co-branding as the identity of creative economy products for business actors. Therefore, this study was conducted to determine the concept of using a brand as co-branding in Law Number 20 of 2016 concerning Brands and Geographical Indications and the views of stakeholders in Bangkalan Regency regarding the implementation of co-branding regulations in the future. The research method used is empirical juridical. The approaches used in this study are factual approaches and statutory approaches. The results of this study indicate that the use of brands as co-branding is closer to the concept of collective brands. Regional legal products in Bangkalan Regency regarding brand protection have not yet had a discourse on the creation and regarding the concept of using brands as co-branding related to creative economy products.